The Oleic/Linoleic Acid Ratio in Olive (Olea europaea L.) Fruit Mesocarp Is Mainly Controlled by OeFAD2-2 and OeFAD2-5 Genes Together With the Different Specificity of Extraplastidial Acyltransferase Enzymes - Hernández, M. Luisa; Sicardo, M. Dolores; Belaj, Angjelina; Martínez-Rivas, José M. (Frontiers in Plant Science, 2021)
Fatty acid composition of olive oil has an important effect on the oil quality so that oils with a high oleic and low linoleic acid content are superior from a nutritional and technological point of view. In the present work, we have first studied the diversity of the fatty acid composition in a set of eighty-nine olive cultivars from the Worldwide Olive Germplasm Bank of IFAPA Cordoba (WOGBC-IFAPA), and in a core collection (Core-36), which includes 28 olive cultivars from the previously mentioned set. Our results indicate that oleic and linoleic acid contents displayed the highest degree of variability of the different fatty acids present in the olive oil of the 89 cultivars under study. In addition, the independent study of the Core-36 revealed two olive cultivars, Klon-14 and Abou Kanani, with extremely low and high linoleic acid contents, respectively. Subsequently, these two cultivars were used to investigate the specific contribution of different fatty acid desaturases to the linoleic acid content of mesocarp tissue during olive fruit development and ripening. Fatty acid desaturase gene expression levels, together with lipid analysis, suggest that not only OeFAD2-2 and OeFAD2-5 but also the different specificities of extraplastidial acyltransferase enzymes are responsible for the variability of the oleic/linoleic acid ratio in olive cultivars. All this information allows for a breakthrough in the knowledge of the linoleic acid biosynthesis in different olive cultivars, which can impact olive breeding programs to improve olive oil quality.